(untitled) (International Journal of Social Research & Innovation, 2022)
The experience of hybrid teaching presented in this paper was shaped by the emergency remote teaching during the Covid-19 pandemic, the affordances of which allowed us to redesign our program to a hybrid mode. In particular, the study highlights strengths, and weaknesses which need to be addressed in curriculum, pedagogy, and technology; to ensure students become successful learners, in hybrid learning contexts. An online survey questionnaire was administered to collect both numerical and written data. Fourteen lecturers who taught in hybrid modality in September 2021 semester at Centre for Foundation Studies at Villa College, and 132 randomly chosen out of the 508 enrolled students participated in this study. The findings of the survey highlighted various challenges faced by the lecturers such as difficulty in engaging with the students, technical issues, and poor student engagement. Similarly, the students noted that they faced various difficulties such as unaffordability of the internet and lack of confidence to interact. Thus, the results prompted a need to further train the lecturers and students on hybrid teaching and learning. Further, the institution needs to establish a mechanism to provide better internet access such as introducing affordable internet packages for the students and develop strategies to support remote students more effectively. The significance of this research is that following the suggested recommendations may aid in enhancing the current hybrid modality experience for both the lecturers and students.